2006
DOI: 10.1159/000092120
|View full text |Cite
|
Sign up to set email alerts
|

Are Short Boys with Constitutional Delay of Growth and Puberty Candidates for rGH Therapy according to FDA Recommendations?

Abstract: Background/Aims: According to FDA-approved guidelines, boys whose height predictions fall to 160 cm or less are considered for treatment with recombinant growth hormone (rGH). The aim of this study was to analyze the value of different height prediction methods by accurately identifying those boys with constitutional delay of growth and puberty (CDGP) in whom final height (FH) prognosis was poor (≤160 cm) and who might therefore be candidates for this treatment modality. Methods: In 69 boys with CDGP diagnosed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 41 publications
(33 reference statements)
0
5
0
1
Order By: Relevance
“…13 Those boys whose height predictions fall below160 centimeters, are candidates for treatment with recombinant growth hormone (rGH) according to FDA-approved guidelines is under investigation. 14 …”
Section: Introductionmentioning
confidence: 99%
“…13 Those boys whose height predictions fall below160 centimeters, are candidates for treatment with recombinant growth hormone (rGH) according to FDA-approved guidelines is under investigation. 14 …”
Section: Introductionmentioning
confidence: 99%
“…However, none of the available methods of prediction are sufficiently sensitive to reliably recruit 14 to 16-year- old boys with CDGP whose final Ht will fall at or below 160 cm. [6870] Before the onset of puberty, many boys with CDGP are short (HtSDS < -2) and have delayed bone age versus their chronological age. GH treatment for boys ( n = 36) with non-familial short children with delayed bone age, started at an average age of 9.3 years (using 0.6 U/ kg/ week divided on daily doses) resulted in a Ht gain of 1.4 SD at the final Ht.…”
Section: Other Forms Of Treatmentmentioning
confidence: 99%
“…The use of clonidine in children with CGDP has been the subject of several studies [8,9] but, very divergent results have been reported and therefore the effectiveness of clonidine in increasing growth rate of CGDP is not clear. Many subjects affected by constitutional short stature show a good response to human growth hormone (HGH) therapy, whereas others do not benefit by this treatment [10][11][12][13]. The use of aromatase inhibitors and oxandrolone, a weak anabolic steroid has been shown to be effective in children with CGDP.…”
Section: Introductionmentioning
confidence: 99%